Analysis of serum pharmacochemistry of hederagenin using UPLC-Q-TOF/MS - Yang, Meng; Wang, Jing (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study investigated the changes of plasma absorbed components in rats after oral administration of hederagenin. Serum pharmacochemistry analysis of hederagenin was carried out to understand the changes of its metabolic components in the body. Biological samples were collected and then the migration components of hederagenin-containing serum were established by UPLC/Q-TOF-MS technique. Possible metabolites were obtained for comprehensive analysis through relevant studies and the regulation of broken bonds in the molecular structure of hederagenin. At about 10.262 min, the molecular ion peak of the hederagenin of M/Z 471[M-H]- was detected in negative ion mode and the prototype product and its associated fragment ions could be detected only at 1, 3, 6, 9, 12, and 24 h after administration. Seventy-one signal peaks of potential metabolites were found in the drug serum. Based on the bond energy characteristics of molecular structure, 47 possible metabolite-related molecular ion peaks through decarboxylation, dehydration, demethylation or methyl shift, deoxygenation, ring opening, and unsaturated biformation were deduced, and signals of 35 metabolite-related molecular ion peaks were identified. Hederagenin can metabolize many products in vivo. Important information about the metabolism of hederagenin, which is useful for fully understanding its mechanism of action, was provided in this study.